Performance Evaluation of Irrigation Networks Based on Sentinel-2 Satellite Imagery and E-PAKSI Data: Vegetation Index Analysis of Water Distribution Efficiency - meny sriwati; Wahiddin; Firman's Bramadhani (CV. Get Press Indonesia, 2026)
The pervasive inefficiency of water distribution in surface irrigation networks necessitates a transition toward objective, data-driven performance auditing. This study aims to develop an evidence-based evaluation model that quantifies the direct impact of irrigation infrastructure physical conditions on agricultural productivity. The research evaluates the nexus between infrastructure integrity and biophysical crop performance by integrating the E‑PAKSI digital database with Sentinel‑2 multispectral imagery. Conducted in the Rentang Irrigation Area, West Java, the study utilized a stratified random sampling of 215 tertiary blocks to analyze spatial variability from head to tail reaches. Vegetation health was quantified using NDVI and SAVI indices, which were subsequently correlated with the physical condition scores of regulatory structures. Results indicate a significant positive correlation (; ) between infrastructure quality and peak vegetation indices. Findings reveal that degraded tertiary gates in downstream sectors trigger water losses of up to 41.50% and planting delays of 25 days. These results imply that rehabilitation priorities must shift toward tail‑end regulatory assets to enhance distributional equity. Practically, these findings provide a strategic roadmap for irrigation authorities to prioritize budget allocations for distal gate repairs, which can potentially recover nearly half of current conveyance losses. In conclusion, the integration of satellite‑derived metrics and digital audits provides a robust framework for Irrigation Modernization 4.0, offering a foundation for future predictive maintenance models using artificial intelligence.